Migration Background and School Tracking: Is there a Double Disadvantage for Second-Generation Immigrants? - Elke Lüdemann; Guido Schwerdt (Verein für Socialpolitik, 2010)
Research on educational disadvantages of second-generation immigrants largely focuses on differences in student achievement tests. Exploiting data from the German PIRLS Extension, we provide evidence that second-generation immigrants face an additional disadvantage when tracked into different types of secondary school. We find that second-generation immigrants are less likely to receive a teacher recommendation for a higher school track. This difference cannot be attributed to differences in test scores or general intelligence alone. Based on these results, we argue that migrant-native test score gaps likely underestimate educational inequalities in tracked school systems.
Keywords: I21; J15; I28; 330; Immigration; Educational Inequalities; School Tracking; Germany